Conspecific and heterospecific host discrimination in two parasitoid species of the mealybug Pseudococcus viburni, the solitary Leptomastix epona and the gregarious Pseudaphycus flavidulus - Karamaouna, F.; Copland, M.J.W. (ENTOMOLOGIA HELLENICA, 2009)
Leptomastix epona (Walker) and Pseudaphycus flavidulus (Brèthes) (Hymenoptera: Encyrtidae) are endoparasitoids of the mealybug Pseudococus viburni (Signoret) (Hemiptera: Pseudococcidae). Leptomastix epona is a solitary parasitoid originating from Europe and P. flavidulus is a gregarious parasitoid from South America. Conspecific and heterospecific host discrimination was examined between unparasitised female adult mealybugs and others already parasitized, at different time intervals between the primary and the following oviposition. Female wasps of L. epona discriminate between unparasitized hosts and hosts parasitized 0-96 hours previously by a conspecific selecting more often the first over the latter for oviposition. Females of P. flavidulus discriminate between unparasitized hosts and hosts parasitized prior to 0-72 hours by a conspecific. Conspecific superparasitism also occurs in both parasitoid species. The secondary sex ratio of L. epona and the clutch size of P. flavidulus are not affected by superparasitism whereas the secondary sex ratio of P. flavidulus in superparasitized hosts is more male biased than in single parasitized hosts. The solitary parasitoid L. epona does not discriminate between unparasitized hosts and hosts parasitized by P. flavidulus 0-3 or 24 hours previously. Nevertheless the gregarious parasitoid P. flavidulus discriminates between unparasitized hosts and hosts parasitized by L. epona 0-3 hours earlier, but it oviposits without discrimination in hosts heterospecifically parasitized 24 hours beforehand. When multiparasitism occurs at 0-3 hours after the first oviposition, L. epona is a superior competitor regardless of which species oviposits first. However, when the time interval between the two ovipositions is 24 hours, the probability of the offspring of P. flavidulus winning the competition with L. epona increases when either species oviposits first. The potential effect of multiparasitism on parasitoid coexistence is discussed in relation to prospects for multiplespecies introductions or augmentative releases for the biological control of the mealybug.